Justification and formalization of approach to regional environmental safety evaluation - Bezsonov, Yevhen; Andreev, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2016)
The analysis of causation in the «man – nature» system is performed and their inextricable connection is proved. The approach to implementation of the concept of sustainable development with emphasis on environmental safety is proposed and justified. Human interests and needs are considered as having priority in the development process, but can be implemented only by ensuring the environmental safety of natural systems on which humanity depends entirely and an integral part of which it is. The potential and actual environmental and economic damage resulting from unsustainable use of natural resources is evaluated. Thus, beekeeping accounts for about 3 % of the gross regional product of Ukraine today, and the regression of fisheries in the Mykolaiv region is thousands of gigacalories. The scheme for determining the potential mortality factor, which is the main indicator in the environmental safety index evaluation is proposed. The scheme describes the functional dependence of organisms on the pollutant concentration. The study is based on the assumption that a person continues to be a central concern in the development process on the basis of tolerance towards other living beings, regardless of their value to human civilization. This approach to provision and control of environmental safety will allow more efficiently and systematically analyze the impact of the human economy on the functional stability of natural systems. It is proved that the safety of human existence in the ecological system will be the greatest under safe living conditions for the most human impact sensitive living component of the environment. The system of regional environmental safety evaluation is based on the environmental characteristics of stenobionts and theoretical principles of the Shelford’s law of tolerance and complication. The methods for estimating the environmental safety index of abiotic and biotic components of ecosystems, the essence of which is to study the biological features of stenobionts, physical and chemical properties and parameters of the abiotic environment are proposed.